ANALISIS TINGKAT KEPUASAN PELANGGAN TOYOTA ATAS RELATIONSHIP MARKETING DAN LAYANAN PURNA JUAL PADA PT. AGUNG TOYOTA SUTOMO DI PEKANBARU - Syahputra, Dedi; Nursanti, Aida; Musfar, Tengku Firli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. General Toyota Sutomo in Pekanbaru with the aim to identify and analyze the Toyota Customer Satisfaction on Relationship Marketing and Sales Service at PT. General Toyota Sutomo in Pekanbaru. This study uses primary data obtained from interviews and giving questionnaires to all employees of PT. General Toyota Sutomo in Pekanbaru. Secondary data were obtained relating to the object and the organizational structure of the population in this study were all employees amounted to 140 people and sampled. The analytical method used in this research is descriptive method. From the testing that has been done by the method Diskriftif, after-sales service variables are variables that have the greatest degree of satisfaction which consists of indicators, Giving insurance, care services, repair services providers, product usage instructions, existence of the company's attention. The level of customer satisfaction at PT. General Toyota in Pekanbaru including quite appropriate classification. This is reflected in the results of the analysis of the suitability and performance levels.Keyword: Level of Customer Satisfaction, Relationship and Sales Service